RESPON TANAMAN PAKCOY (Brassica rapa L.) TERHADAP PEMBERIAN SERBUK KAYU DAN PUPUK PETRORGANIK - Nugroho, Heru; Sembiring, Jefri; Kusumah, Rangga; Yusuf, Mani; Anwar, Anwar; Endrawati, Tri (Universitas Islam Balitar, 2024)
One effort that can be made to improve soil fertility is by providing rich and petroganic powders. This research aims to determine the growth response of pakcoy plants to a combination of wood dust and petrorganic fertilizer treatments. This research was carried out from April to July 2023 in Sumber Rejeki Village, Merauke. This research used a randomized block design. The variables observed were plant height, number of leaves, leaf length, leaf width, and wet weight. The results of the research showed that the combination of sawdust and petroganic treatments had a different effect on each variable of pakcoy plant growth. The highest treatment on the plant height variable was obtained in the treatment without rich powder + 1 t.ha-1 petroganic fertilizer, the number of leaves in the sawdust treatment was 20 t.ha-1 + 3 t.ha-1 petroganic fertilizer, the leaf length was found in the treatment without wood dust + petroganic fertilizer 1 t.ha-1, leaf width was found in the treatment without sawdust + petroganic fertilizer 1 t.ha-1 and wet weight was found in the wood powder treatment 10 t.ha-1 + petroganic fertilizer 3 t.ha-1.